LEVEL OF PREGNANT WOMEN'S KNOWLEDGE ABOUT DELIVERY AID AND MOTHER'S ATTITUDES IN CHOOSING A DELIVERY HELP IN KRUENG THO VILLAGE, DARUL HIKMAH DISTRICT, ACEH JAYA DISTRICT - Zahara, Hafni; Afridah, Afridah; Indy, Elsa (Transpublika Publisher, 2023)
Childbirth is an important event that is always remembered in a woman's life. The choice of place of delivery will have an impact on the health of the birthing mother. Even though it is supported by good facilities and health workers, it is still found that births are carried out by health workers at home, this happened in Krueng Tho Village, Aceh Jaya Regency. The aim of this research is to analyze the level of knowledge of pregnant women and the attitudes taken in choosing a place of delivery in Krueng Tho Village, Darul Hikmah District, Aceh Jaya Regency. The sample in this study was part of pregnant women in 2011 and 2023. This research is a quantitative type with descriptive analytical methods. Determining the sample size in this study was calculated using a formula of 150 people. The sampling technique uses total sampling. Factors that influence the choice of place and delivery assistance include level of knowledge, income level, attitude, level of education, family support, distance to health facilities and age factors. It is hoped that this research can provide advice for health workers to pay more attention to pregnant women and women giving birth, especially in terms of choosing a place of birth and birth assistance, namely the need to increase attention to health service programs through socializing childbirth in health facilities.